2018
DOI: 10.1038/s41598-018-33714-2
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive portrait of Y-STR diversity of Indian populations and comparison with 129 worldwide populations

Abstract: India, known for its rich cultural, linguistic and ethnic diversity, has attracted the attention of population geneticists to understand its genetic diversity employing autosomal, Y-chromosomal and mitochondrial DNA markers. Y-chromosomal short tandem repeats (Y-STRs) are useful in understanding population substructures and reveal the patrilineal affinities among populations. Previous studies on Indian populations based on Y-STR markers were either limited to restricted number of markers or focused on few sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…YHRD tools were used to perform AMOVA based on R ST and MDS was performed to infer the genetic relationship among the various populations 19 . For comparison of patrilineal affinities with Indian populations, Y-STR data from our laboratory was included 15 , whereas for comparison with populations from neighboring countries, published data was incorporated 18 (Supplementary Table S1). Male individuals from both the populations were assigned haplogroups based on the Y-STRs employing Whit Athey's haplogroup predictor tool 44 .…”
Section: Pcr Amplification Genotyping and Sequencing Autosomal And mentioning
confidence: 99%
See 1 more Smart Citation
“…YHRD tools were used to perform AMOVA based on R ST and MDS was performed to infer the genetic relationship among the various populations 19 . For comparison of patrilineal affinities with Indian populations, Y-STR data from our laboratory was included 15 , whereas for comparison with populations from neighboring countries, published data was incorporated 18 (Supplementary Table S1). Male individuals from both the populations were assigned haplogroups based on the Y-STRs employing Whit Athey's haplogroup predictor tool 44 .…”
Section: Pcr Amplification Genotyping and Sequencing Autosomal And mentioning
confidence: 99%
“…Our previous studies based on analysis of autosomal STRs 14 and Y-chromosomal STRs 15 that included populations from J&K (JK) (other than GJ and LL populations), suggested that JK individuals were not genetically isolated from other populations of India. This observation was in concordance with a previous report 16 .…”
mentioning
confidence: 99%
“…As expected, such similarities reduce the accuracy of STR-based prediction tools. This conclusion is supported in separate studies [37], [38], [40], which suggest SNP analysis as a second validation step if accurate predictions are required. Thus, the most recent studies use a combination of STR and SNP as genetic markers [41], [42] for haplogroup predictions.…”
Section: Introductionmentioning
confidence: 58%
“…From the intercontinental perspective, a MDS was performed between Maoming Han and 21 worldwide populations (Kim et al, 2001;Miranda et al, 2001;Roewer et al, 2005;Mizuno et al, 2008;Alam et al, 2010;Laouina et al, 2011;Wolfgramm Ede et al, 2011;Ramos-Luis et al, 2014;Xu et al, 2015;Han et al, 2016;Rapone et al, 2016;Wang et al, 2017;Alonso Morales et al, 2018;Fan et al, 2018c;Singh et al, 2018;Henry et al, 2019;Lang et al, 2019;Li et al, 2019;Salvador et al, 2019;Reid and Heathfield, 2020). As shown in Supplementary Figure 1, (Yang et al, 2014;Shu et al, 2015;Han et al, 2016;Wang et al, 2016Wang et al, , 2017Xu et al, 2016;Yao et al, 2016;Jiang et al, 2017;Chen et al, 2018;Fan et al, 2018c;Lang et al, 2019;Yin et al, 2020) are listed in Supplementary 2B).…”
Section: Genetic Differences Between Maoming Han and Han Chinese Populations From Southern And Northern Mainland Chinamentioning
confidence: 99%